MAIN PROPERTIES AND APPLICATIONS OF POLYMERIC COMPOSITE MATERIALS - Safarova M. (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article shows various groups of modern polymer composite materials, their composition and applications. Their general classification is determined by the reactivity of binders and fillers, applicable to dispersed, fibrous or laminated materials. The classification is based on the most common thermosetting matrix materials and the most common fillers.